Analysis of Student Misconceptions in Working on Algebraic Form Counting Operations Using Certainty of Response Index - Angjelina, Grace; Hidayat, Edi; Muslim, Siska Ryane (Jurnal Pendidikan MIPA, 2021)
This study aim is to determine the misconceptions that occur in students and the factors that cause students to experience misconceptions in the material of algebraic arithmetic operations. The research which was conducted at SMP Negeri 4 Tasikmalaya class VII C with a total of 32 students was a qualitative research with a descriptive approach. The subjects of this study were taken purposively, namely 5 students of class VII C of SMP Negeri 4 Tasikmalaya. The data collection technique consisted of a misconception analysis test accompanied by the Certainty of Response Index (CRI) and interviews. Data analysis techniques consisted of data reduction, data presentation, and verification. Based on the results of data analysis, it is concluded that (1) S4 misconception of equations, S10 misconception of operations, S17 misconceptions of variables, S28 misconception of fractions, S10 misconceptions of negative signs (2) The causes of misconceptions that occur include incorrect student preconceptions, student associative thinking, humanistic thinking, incomplete reasoning, incorrect intuition, student abilities and student interest in learning. Keywords: Certainty of response index, misconceptions, algebraic form counting operations.  DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp52-66